Allergenic Properties and Molecular Characteristics of PR-1 Proteins - Wangorsch, Andrea; Scheurer, Stephan; Blanca, Miguel; Blanca-Lopez, Natalia; Somoza, María Luisa; Martín-Pedraza, Laura (Frontiers in Allergy, 2022)
Only a small fraction of proteins in plants and animals are classified as allergens. The allergenic properties frequently are attributed to certain functional characteristics of the proteins, such as a role in the plant defense against biotic and abiotic stress to achieve systematic acquired resistance. In line with this, members of eight out of 17 functional pathogenesis-related protein (PR) families have been characterized as allergens. The present review summarizes molecular features and allergenic significance of allergens of the PR-1 family. Not many allergens have been identified as belonging to this protein family, most of them having a pollen origin, like mugwort or Bermuda grass. Molecular and structural features of allergenic PR-1 proteins are discussed and attributed to their IgE-reactive properties, clinical manifestation and cross-reactivity among different foods and inhalants.